Influence of Sn4+ substitution on the Ba(Zn1/3Nb2/3)1-xSnxO3 (0 ≤ x ≤ 1) perovskites: Doping mechanism, structural and dielectric properties - Feng, Y.; Tan, Kar Ban; Sulaiman, Y.; Lim, H.N.; Chan, K.Y.; Chang, S.K.; Lu, M.; Han, W.J. (Elsevier, 2025)
Herein, we investigated the chemically modified Ba(Zn1/3Nb2/3)1-xSnxO3 (0 ≤ x ≤ 1) perovskites synthesised by solid-state reaction from the perspectives of doping mechanisms, microstructural and dielectric properties. The Rietveld refinement analysis affirmed that these perovskites possess a cubic structure with a space group of Pm 3‾ m. The polyhedral grains ranged from 225 to 88 nm, exhibiting a gradual decrease due to increasing Sn4+ concentration. Meanwhile, the chemical stoichiometry and oxidation states of the constituent elements were validated by the elemental analyses using ICP-OES, EDS and XPS, respectively. The FT-IR spectra displayed a slight blue shift related to the NbO6 octahedra; whilst, the Raman spectroscopy confirmed a vibration of SnO6 octahedra. A strong correlation was observed between the dielectric properties and various factors including pellet density, polarisation per molar volume, packing fraction and bond valence sum. Notably, the impedance study revealed the behaviours of negative temperature coefficient of resistance (NTCR) and non-Debye relaxation in these perovskites. The AC conductivity was also found to follow a conduction barrier hopping (CBH) model over the temperature range of 500–700 °C, suggesting that the charge carrier could be attributed to double ionised oxygen vacancies (Vo••) in the host structure.